(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The phenomenon of “boilover” in storage tanks containing petroleum products is among the most hazardous events that can occur during large-scale fires. When water is present at the bottom of the tank, the burning hydrocarbon layer may cause a sudden evaporation of the water, followed by a violent ejection of hot liquid and a massive fireball. This scenario poses severe threats to personnel safety, facility integrity, and environmental protection. Given the increasing global demand for petroleum-based fuels and the continued use of large above-ground storage tanks, understanding and mitigating the risks associated with boilover has never been more critical. The primary objective of this study is to clarify how two key parameters - time to boilover and mass burning rate - influence both prevention and response strategies during petroleum product tank fires. The research employs a combination of experimental data analysis and critical literature review to assess how these parameters correlate with the escalation of fire events. The experiments, conducted under controlled laboratory conditions, measured the influence of fuel properties, water layer thickness, and burning surface area on boilover onset and burning intensity. Based on these findings, the study synthesizes the most applied structural (e.g., tank design, insulation, drainage systems) and operational (e.g., cooling tactics, fuel-level monitoring, emergency response timing) fire protection strategies. Emphasis is placed on how real-time assessment of the mass burning rate and the predicted time to boilover can inform decision-making during emergencies. The results show that the earlier identification of critical thresholds significantly enhances the effectiveness of intervention measures. Moreover, certain prevention methods - such as early cooling and drainage - can delay or even prevent boilover if applied in a timely manner. Ultimately, this study bridges the gap between theoretical fire behavior parameters and practical fire safety management, offering a more predictive and data-driven approach to handling storage tank fires.